Coupling of spectroscopy and nitrogen-oxygen isotopes unveils the mechanisms of dissolved organic matter and nitrate pollution in lakes within the agro-pastoral transition zone - Guodong Chai; Fang Yang; Haiqing Liao; Debin Jia; Weiying Feng; Chiamin Ho; Dongpin Liu; Shuling Chen; Jianguo Liu; Huibin Yu (Journal of Environmental Sciences, 2026)

Quasi-solid-state electrolytes enabling long-life flexible electrochromic energy storage smart windows - Li Liao; Shuling Xiang; Biyou Bao; Guanglong Xu; Chengli Zhang; Qiang Wang; Zhenhu Cao; Wentao Chen; Hongtao Cao; Hongliang Zhang (Chemical Engineering Journal, 2026)

A New Sphalerite Thermometer Based on Machine Learning with Trace Element Geochemistry - Hongtao Zhao; Yu Zhang; Yongjun Shao; Jia Liao; Shuling Song; Genshen Cao; Ruichang Tan (Natural Resources Research, 2024)

Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p

A review of the advances and prospects of aqueous Dual-Ion batteries - Shuhua Guan; Qiaoling Peng; Xiuli Guo; Ye Zheng; Enda Liao; Shuling Sun; Kyungsoo Shin; Botian Liu; Xiaolong Zhou; Caineng Zou; Yongbing Tang (Chemical Engineering Journal, 2024)

Insights into the catalytic mechanism of V-Mo@CN for the oxidation of 5-hydroxymethylfurfural to 2,5-diformylfuran - Shibo Yang; Tong Sun; Xiaokai Li; Wenbo Liao; Jianfei Bian; Xing Tang; Shuling Yang; Lu Lin; Wei Jiang; Lincai Peng; Yong Sun (Chemical Engineering Journal, 2024)

Effects of Fermented Cottonseed Meal Substitution for Fish Meal on Intestinal Enzymatic Activity, Inflammatory and Physical-Barrier-Related Gene Expression, and Intestinal Microflora of Juvenile Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Xiaolin Huang; Heizhao Lin; Maoyan Luo; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2023)
The present study was conducted to investigate the effects of dietary fermented cottonseed meal (FCSM) substitution for fish meal on intestinal enzymatic activity, inflammatory and physical-barrier-related gene expression, and intestinal microflora of juvenile golden pompano. The 375 golden pompanos were divided into 15 groups of 25 fish each, with three replicates for each experimental group. The fish were fed five experimental diets (0 (FM), 12.5% (CSM12.5), 25% (CSM25), 50% (CSM50), and 100% (CSM100) substitution levels) for 8 weeks. The fish were reared and fed the experimental diets under a natural-day light cycle. Compared with the control group, the activities of AMY (amylase) enzymes in the CSM12.5 group and all other groups were elevated (p

Trade drives leakage of life-cycle carbon dioxide emissions from plastics in China over 2010–2021 - Hao Ding; Shuling Liao; Donghai Tu; Pei Hua; Jin Zhang (Journal of Cleaner Production, 2023)

Effect of urea feeding on transforming and migrating soil fluorine in a tea garden of hilly region - Hua Long; Yamei Jiang; Chaoqun Li; Shuling Liao; Shuyu Shi; Chunping Huang; Shilin Zhao; Xiaoting Li; Yang Liao (Environmental Geochemistry and Health, 2021)